Pseudomonas chlororaphis IRHB3 assemblies beneficial microbes and activates JA-mediated resistance to promote nutrient utilization and inhibit pathogen attack - Wei, Dengqin; Zhu, Dan; Zhang, Yunfeng; Yang, Zheng; Hu, Yu; Song, Chun; Yang, Wenyu; Chang, Xiaoli (Frontiers in Microbiology, 2024)
Introduction The rhizosphere microbiome is critical to plant health and resistance. PGPR are well known as plant-beneficial bacteria and generally regulate nutrient utilization as well as plant responses to environmental stimuli. In our previous work, one typical PGPR strain, Pseudomonas chlororaphis IRHB3, isolated from the soybean rhizosphere, had positive impacts on soil-borne disease suppression and growth promotion in the greenhouse, but its biocontrol mechanism and application in the field are not unclear. Methods In the current study, IRHB3 was introduced into field soil, and its effects on the local rhizosphere microbiome, disease resistance, and soybean growth were comprehensively analyzed through high-throughput sequencing and physiological and molecular methods. Results and discussion We found that IRHB3 significantly increased the richness of the bacterial community but not the structure of the soybean rhizosphere. Functional bacteria related to phosphorus solubilization and nitrogen fixation, such as Geobacter, Geomonas, Candidatus Solibacter, Occallatibacter, and Candidatus Koribacter, were recruited in rich abundance by IRHB3 to the soybean rhizosphere as compared to those without IRHB3. In addition, the IRHB3 supplement obviously maintained the homeostasis of the rhizosphere microbiome that was disturbed by F. oxysporum, resulting in a lower disease index of root rot when compared with F. oxysporum. Furthermore, JA-mediated induced resistance was rapidly activated by IRHB3 following PDF1.2 and LOX2 expression, and meanwhile, a set of nodulation genes, GmENOD40b, GmNIN-2b, and GmRIC1, were also considerably induced by IRHB3 to improve nitrogen fixation ability and promote soybean yield, even when plants were infected by F. oxysporum. Thus, IRHB3 tends to synergistically interact with local rhizosphere microbes to promote host growth and induce host resistance in the field.